NMARQ Ablation for Atrial Fibrillation: Results from a Multicenter Study. (16th June 2015) - MAHIDA, SAAGAR; HOOKS, DARREN A.; NENTWICH, KARIN; NG, G. ANDRE; GRIMALDI, MASSIMO; SHIN, DONG‐IN; DERVAL, NICOLAS; SACHER, FREDERIC; BERTE, BENJAMIN; YAMASHITA, SEIGO; DENIS, ARNAUD; HOCINI, MÉLÈZE; et al.
nMARQ AF Ablation Background nMARQ is a multipolar catheter designed to simultaneously ablate at multiple sites around the pulmonary vein (PV) circumference with a single radiofrequency application. We sought to define the safety and efficacy of atrial fibrillation (AF) ablation with the nMARQ catheter. Methods In a multicenter study, patients with drug‐refractory AF were included. Procedural outcomes were documented at 1 year. Results 374 patients underwent PV isolation using nMARQ (age 60 ± 10 years, 264 male), of whom 263 patients had paroxysmal AF (PAF), while 111 patients had persistent AF. A total of 1, 468 of 1, 474 veins (99.6%) were isolated with the nMARQ catheter alone. Thirty‐five (13%) PAF patients and 30 (27%) persistent AF patients underwent additional ablation at non‐PV sites (2.4 ± 1.4 non‐PV sites). Procedure time for PV isolation only was 1.9 ± 0.7 hours (fluoroscopy 24 ± 14 minutes). Procedure time for PV isolation and non‐PV ablation was 2.4 ± 1.0 hours (fluoroscopy 30 ± 23 minutes). Major adverse events occurred in two patients (0.5%); one esophago‐pericardial fistula and a second, mortality due to sepsis of unknown cause. One‐year follow‐up data were available in 65 (25%) PAF and 20 (18%) persistent AF patients. Forty‐two (65%) PAF and 13 (65%) persistent AF patients were free of arrhythmia at 1 year. In patients undergoing repeat procedures (n = 17) the most frequent points of PV reconnection were: anterior RSPV, inferior RIPV, and superior LSPV. Conclusions AF ablation with nMARQ is associated with short procedure times and high acute success rates. Further research is necessary to more clearly define long‐term outcome.